Illuminating the North Korean nuclear explosion test in 2017 using remote infrasound observations. Issue 1 (20th August 2021) - Che, Il-Young; Kim, Keehoon; Le Pichon, Alexis; Park, Junghyun; Arrowsmith, Stephen; Stump, Brian
SUMMARY: North Korea conducted its sixth underground nuclear explosion test (${m_ b}$ 6.3) on 2017 September 3. The underground explosion produced substantial low-frequency atmospheric waves, which were detected by infrasound arrays located up to a distance of 566 km. These infrasound waves are formed by the conversion of seismic energy to acoustic energy across the lithosphere–atmosphere interface. While infrasound records at regional distances produce estimates of ground motion amplitude over spatially extended regions covering about 26 500 km 2, 3-D full seismo-acoustic simulations within the lithosphere and atmosphere provide quantitative information about seismo-acoustic energy partitioning. Our results demonstrate the capability of remote infrasound observations combined with 3-D propagation modelling to further develop discrimination methods for underground sources. These results contribute to enhance the confidence of source identification and characterization in nuclear test monitoring research, which is essential for the enforcement of the Comprehensive Nuclear-Test-Ban Treaty.